Modern electronic media and the arab spring – 2011 - Myamesheva, G.; Davydova, I. (Journal of Oriental Studies, 2016)
In the informational society era the role of information is growing quickly. Modern media have a wide diapason and spectrum of activity. In the context of globalization the media turns into the fi rst power instead of the fourth. Modern media is not only to inform, but also to entertain and shape public opinion. . The Internet creates a special media environment, which is similar to television, radio and print media. Features of the electronic media: constant audience, media effi ciency (regularly updating websites, instant access to information), constant feedback from the audience (forums, voting, polls, conferences, guestbook). Social media are widely used in political life of different countries, both from politicians’ side and other subjects of political activity. First of all, these subjects are educated young people, knowing the high-tech technologies. Under this scenario happened the events of the Arab spring of 2011 .